“Il en faut un peu”: Farm Women and Feminism in Québec and France Since 1945 - Cuthbert Brandt, Gail; Black, Naomi (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractCertain farm women's organizations continue to represent the social feminist tradition of Canadian suffragism and the broader social Catholic feminism still influential elsewhere. Canadian historians have often criticized such groups in contrast with a more aggressive, equal-rights feminism found among urban and rural women in both waves of feminism. We argue that, far from being conservative, groups identified as social feminist serve to integrate farm women into public debates and political action, including feminism. We outline the history of the Cercles de fermières of Québec, founded in 1915, and the French Groupements de vulgarisation-développement agricoles féminins, founded since 1959. A comparison of members with nonmembers in each country and across the group, based on survey data collected in 1989 for 389 cases, suggests that club involvement has counteracted demographic characteristics expected to produce antifeminism. In general, we find less hostility to second-wave feminism than might be expected. Relying mainly on responses to open-ended questions, we argue that, for our subjects, feminism is tempered by distaste for confrontation. Issues supported by the movement for women's liberation are favoured by farm women, but the liberationist style and tactics are eschewed. Those of our respondents identified as feminists express preference for a complementarity modelled on the idealized family.